(untitled) (Global Journal of Science Frontier Research, 2012)
In this study, three fungi isolated from some hospitals at Makkah Almoukarramah showed promising degrading capabilities towards some anesthesia drugs (propofol, clonazepam, lidocaine and bucaine ) commonly used. Based on polyphasic identification , morphological, biochemical and 18SrRNA molecular identification these isolates are nominated as Aspergillus niger, A. fumigatus and Rhizopus oryzae. In general, propofol and clonazepam, were more liable to the biodegradation process when compared to the other two drugs. A. fumigatus showed the highest degrading capability towards drugs. The highest fungal wet biomass of A.fumigatus was obtained on cultures containing propofol and clonazepam at a final concentration of 2.5 and 1.25mgml-1, respectively and separately. Shaking cultures showed an enhanced degradation when compared to that of static cultures. Moreover, the optimal conditions for drug biodegradation by A.fumigatus were pH4 at 28.5Cº and addition of vitamin C to the growth medium. Calcium alginate- immobilized fungal cells of A. fumigatus grown on propofol and clonazepam containing media showed improved higher degradation of the two drugs, compared to those of free fungal cells growing on the same media. On the other hand, a chromatogram of Infrared (IR) for the end products derived from the biodegradation of drugs confirmed that these two drugs are efficiently degraded to certain end products by A. fumigatus that could be categorized into some identified groups.